Exploring and Predicting Consumer Awareness of Insurance Product Innovation - Ismail, Noraini; Md Husin, Maizaitulaidawati; Ishak, Izzaamirah; Abdul Manaf, Normaisarah (International Journal of Engineering and Technology, 2018)
The purpose of this paper is to explore consumer awareness of insurance product innovation. One area of concern for insurance companies is the lack of focus given to consumer on product innovation awareness. It is possible that this study could shed some light on the possibly to offer some assistance to the insurance companies.â€¨This is an exploratory research paper. A survey method was employed using a sample of 210 respondents, of age between 25 and 55 years old at Klang Valley, Malaysia. This study was conducted using crosstabulation analysis. Based on the findings, it was revealed that mass media plays a vital role to influence consumersâ€™ awareness regarding insurance product innovation. On the other hand, this study also shows that most of the insurance consumers come from Gen Y. Besides, the finding indicates that insurance product is one of the alternatives for consumers saving behaviour. This study provides insights for a previously unaddressed insurance product innovation awareness among consumers. Prior work on consumer awareness and product innovation has not focuses on insurance industry. This study would be useful for insurance companies, as the findings would help them to formulate strategies for promotional activities, which will help to increase demand and market share.Â Â